Sensing particles under the surface with nanoindentation - Lukas Walch; Claus O.W. Trost; Kevin Kutlesa; Jakob Zitz; Thomas Klünsner; Gerald Ressel; Alfred Hackl; Megan J. Cordill; Stanislav Zak (Materials & Design)
Nanoindentation is a widely used material characterization technique. However, the interaction of different phases in multi-phase materials and their influence on measurement results is often only insufficiently considered. In particular, the question of how, and to what degree, hard phases embedded invisibly beneath the surface of a softer matrix affect the load–displacement curves during nanoindentation was unexamined. To address this issue, nanoindentation mapping was performed near the edge of cubic samples made from high-speed steel composed of a soft metal matrix and hard primary carbides. The high-speed steels’ heat treatment was varied to achieve two microstructurally distinctive material states featuring: I.) small, tightly-spaced, and II.) large, widely-spaced primary carbides. The microstructures below the indents were exposed on cross-sections prepared by focused ion beam milling. The experimental set was complemented by a parameterized two-dimensional axisymmetric finite element model that replicated load–displacement curves for indentations with hard carbide phases located at well-defined depths below the indenter. The ratio of the indenter tip’s contact depth to the carbide’s depth was used to quantify the effect of sub-surface carbides on apparent material properties. Above ratios of 0.2 and 0.3, the reduced elastic modulus, respectively hardness, were significantly higher than pure matrix values.